PERILAKU PATOLOGIS PADA KISAH NABI MUSA DAN ‘ABD DALAM ALQURAN: Telaah Epistemologi al-Jâbirî dan Semiotika Peirce - Mushodiq, Muhamad Agus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to explore pathological or deviation behaviors found in the story of Moses and ‘Abd or Khidir in the Qur’an of surah al Kahf. More specifically, this study is projected to find the basis of all pathological behavior based on al-Jâbirî’s epistemology. To understand the behavior of deviation holistically, the researcher uses Peirce semiotics theory and then synergized with al-Jâbirî’s epistemology which includes bayânî, burhânî, and ‘irfânî's reason. Semiotics theory is used as an interpretation of verbal signs related to deviation behavior. Peirce's semiotics theory examines the sign of three points of view, namely representamen, object, and interpretation. The researcher employs qualitative method with the type of library research. The results of this study are: (1) the perforation of a ship is a situational deviation based on pseudo ‘irfânî reasoning, (2) child killing is a situational deviation based on a theological reason with pure ‘irfânî reason, (3) antipathy towards the guest is an organized deviation based on the violation of bayânî reasoning, (4) the prediction of the seizure of the ship by the king is a non situational deviation based on the violation of bayânî reasoning, and (5) plunging the elderly into apostasy and kufr is a non-situational deviation based on the violation of bayânî reasoning.